International Stock market integration: Central and South Eastern Europe compared - Roman Horváth; Dragan Petrovski (Institut für Ost- und Südosteuropaforschung (IOS), 2012)
We examine the international stock market comovements between Western Europe vis-àvis Central (the Czech Republic, Hungary and Poland) and South Eastern Europe (Croatia, Macedonia and Serbia) using multivariate GARCH models in 2006-2011. Comparing these two groups, we find that the degree of comovements is much higher for Central Europe. The correlation of South Eastern European stock markets with developed markets is essentially zero. The exemption to this regularity is Croatia with its stock market displaying a greater degree of integration towards Western Europe recently, but still below the levels typical for Central Europe. All stock markets fall strongly at the beginning of the global financial crisis and we do not find that the crisis altered the degree of stock market integration between this group of countries.
urn:nbn:de:101:1-201207106463
Keywords: 330; stock market comovements; Central and South Eastern Europe; GARCH; Börsenkurs; Preiskonvergenz; Aktienmarkt; Marktintegration; Finanzkrise; Ostmitteleuropa; Südosteuropa; Westeuropa